Community as an Open Site of Adult Education - Bo Chang (Adult Education Research Conference, 2014)
The author analyzed the functions of social units, how adult education serves community, and how non-adult education organizations in community can become adult education sites and provide adult educational services to community. The author argues that community is an open site for adult education; analyzing how adult education serves community and how non-adult education organizations interrelate to adult education will help us locate the adult education opportunities in community and fully integrate the learning resources in community into adult education activities.